The complex determinants of childhood nutritional status and undernutrition in South Africa - Bertscher, Jonathan (University of Cape Town, 2014)
Includes bibliographical references. === I adopt two approaches in estimating a childhood nutrition model. In the first, child nutrition enters as a continuous dependent variable, allowing me to estimate the average marginal effects on childhood nutrition (proxied by three anthropometric measures). The second approach allows me to estimate how the probability of being undernourished changes with variations in the explanatory variables, making use of a limited dependent variable approach - after converting child anthropometry into a binary variable indicating whether or not the child is undernourished. The ultimate purpose of this exercise is to inform those involved in the design of nutrition policy in South Africa as in what measures can be expected to be most effective. In addition, I intend to make interested researchers aware of the complexities involved in an attempt to promote more accurate studies that will serve to further refine child nutrition policy.